Data Management in a Regulatory Context - Grønning, Niels (Frontiers in Medicine, 2017)
With the implementation of Article 57(2) in 2012 the EMA embarked on a digitalization journey that foreseeably would ensure greater product oversight and interoperability across the community. This initiative has subsequently led to additional focus from the agency with respects to the utilization and harmonization of data as part of the regulatory process. Driven by both internal and external factors the EMA have through the EU telematics strategy laid the foundation for the regulatory driven services that may be expected from the community the coming years. Supported by standardisation initiatives (e.g. ISO IDMP) the EMA is gradually building an information management driven approach to data utilization and exploitation within drug evaluation and approval. Primarily driven by the increasing demand for signal detection the EMA is additionally hoping to leverage the establishment of defined information models and supporting controlled terms to safeguard future activities within the community. Collectively the overall community may seek to gain from the overall digitalization roadmap proposed by the EMA and interesting opportunities may be sought as part of the transition. Already now pharmaceutical companies are gradually adapting to this new paradigm and actively seeking to explore how they may leverage the future EMA operating model to serve internal business requirements. If successful, the collective efforts from industry and regulators may lead to an unprecedented product oversight and offer regulators the opportunity to proactively drive corrective actions and therefore improve patient safety.